2017
DOI: 10.1177/0306419017749580
|View full text |Cite
|
Sign up to set email alerts
|

Experiential learning in engineering education: The role of student design competitions and a case study

Abstract: Student competitions can play an important role in education: they promote interest and engagement of the students, as well as of the teachers. In the case of engineering, one of the most challenging contests in Europe is the Motostudent event, joined by the University of Brescia (UniBS) in 2016 for the first time. It is a typical implementation of Kolb's theory of experiential learning, where engineering theory and application meet in an intensive, 'hands-on' team work experience, resulting in a very effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 32 publications
(45 reference statements)
1
35
0
3
Order By: Relevance
“…It appears that design competitions for engineering students suit points 2–3 specifically as they are application projects, point 4 as they promote the so-called soft skills, and point 5 as they motivate self-learning and peer-to-peer learning as well. This is also highlighted in Gadola and Chindamo, 13 a recent paper describing the authors’ own experience through a case study, and stating that among the various benefits, the intensive design, manufacturing, and testing activities related to these competitions have promoted applied research, as shown by the following publications. Vibration testing on a four-poster rig and the development of an experimental suspension friction model, to be incorporated into FSAE vehicle dynamics simulations, are described in Benini et al.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…It appears that design competitions for engineering students suit points 2–3 specifically as they are application projects, point 4 as they promote the so-called soft skills, and point 5 as they motivate self-learning and peer-to-peer learning as well. This is also highlighted in Gadola and Chindamo, 13 a recent paper describing the authors’ own experience through a case study, and stating that among the various benefits, the intensive design, manufacturing, and testing activities related to these competitions have promoted applied research, as shown by the following publications. Vibration testing on a four-poster rig and the development of an experimental suspension friction model, to be incorporated into FSAE vehicle dynamics simulations, are described in Benini et al.…”
Section: Introductionmentioning
confidence: 88%
“…8 FSAE and similar competitions such as MotoStudent, Shell EcoMarathon and RoboCup as an added value that universities should offer to their students within the EU educational framework (EHEA -Framework for the Qualifications of the European Higher Education Area) are described in De Juan et al 9 They are also consistent with the guidelines prescribed by the Dublin Descriptors (2002), consisting in the following statements of typical competence levels to be achieved in higher education: [10][11][12] • Knowledge and understanding • Applying knowledge and understanding • Making judgements • Communication • Learning skills It appears that design competitions for engineering students suit points 2-3 specifically as they are application projects, point 4 as they promote the socalled soft skills, and point 5 as they motivate self-learning and peer-to-peer learning as well. This is also highlighted in Gadola and Chindamo, 13 a recent paper describing the authors' own experience through a case study, and stating that among the various benefits, the intensive design, manufacturing, and testing activities related to these competitions have promoted applied research, as shown by the following publications. Vibration testing on a four-poster rig and the development of an experimental suspension friction model, to be incorporated into FSAE vehicle dynamics simulations, are described in Benini et al 14 Experimental, fourposter-based testing on vehicles is also dealt with in Chindamo et al [15][16][17] A fuzzy logic-based approach to energy management on a hybrid high-performance vehicle is described in Chindamo et al 18 The application of neural networks to a typical problem related to vehicle state estimation in vehicle dynamics is dealt with in Gadola and Chindamo.…”
Section: Introductionmentioning
confidence: 90%
“…Informally, the value of these student competitions is widely known, since it is common for vehicle manufacturers to recruit from these events. In recognition of this value, various attempts have been made to incorporate competitive vehicle teams into formal curricular courses [2,4,5,6,7,9]; many universities offer the option of using a portion of the vehicle design as a capstone project for a small group of students. In addition to the existing capstone option, in 2017-2018 McMaster Engineering introduced the option of using vehicle project work as a technical elective.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, behavioral theories of teaching and learning are not applicable to postgraduate studies on Lean Management because the role of the learner's subjective (personal) experience is ignored, while postgraduate students are often experienced managers. Therefore, postgraduate studies on management and engineering are characterized by a dominant role of the experiential learning approach [27,28]. This has become especially important considering the increasing role of blended and distant learning driven in recent months by the COVID-19 pandemic [29].…”
mentioning
confidence: 99%